Legal Regulation of Campaign Deliberation: Lessons from Brexit - Organ, James (2019)
There has been significant attention paid to explaining and understanding the impact of the UK’s vote to leave the EU on UK politics and its constitution. There has also been criticism of the political campaigning, from both the “leave” and “remain” sides, and of people’s understanding of what they were voting for. There has been limited discussion, though, of how to improve the quality of campaign deliberation, which is fundamental to the legitimacy of both representative and direct democratic processes. Using the UK’s vote on EU membership as a case study, this article examines the importance of the law to regulate and improve deliberation prior to direct public votes on specific policy issues. It also considers options for changes to the law and for its implementation, using the current provisions about false statements in electoral law as a starting point. The article argues that the quality of deliberation during UK referendum campaigns needs to improve and that legal regulation should be developed. There are, however, significant challenges in drafting legislation that appropriately defines and limits the use of misleading statements, and at the same time avoids excessive restriction of free speech, or an excessively political role for regulatory bodies and the courts. Given the nature of political campaigning and the challenges in reducing the use of misleading statements by political actors through legal regulation, increased deliberative opportunities for citizens are proposed as a complementary, perhaps more effective means to positively enhance deliberation in political campaigns. Whatever approach is taken, direct democracy needs to be combined effectively with representative democracy, based on a common underlying principle of the importance of deliberation, and not treated as a separate part of a state’s democracy.